1992
DOI: 10.2307/2404499
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Pesticides on the Germination of Weed Seeds: Implications for Manipulative Experiments

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.. British Ecological Society is collaborating with JSTOR to digitize, preserve and extend access to Journal of Applied Ecology. Summary 1. The effects of three pesticides, chlor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

1994
1994
2018
2018

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 31 publications
0
30
0
Order By: Relevance
“…Furthermore, the two insecticides are not likely to exert phytotoxic or stimulatory effects if applied as recommended (Brown and Gange 1989a;Fraser and Grime 1997;Ganade and Brown 1997;Tomlin 1994). Although Gange et al (1992) reported an inhibition of seed germination by dimethoate for some annual forbs we consider this effect to be of minor importance. First, dimethoate was sprayed on above-ground plant parts and should, therefore, not affect germination of seeds in the soil.…”
Section: Discussionmentioning
confidence: 83%
“…Furthermore, the two insecticides are not likely to exert phytotoxic or stimulatory effects if applied as recommended (Brown and Gange 1989a;Fraser and Grime 1997;Ganade and Brown 1997;Tomlin 1994). Although Gange et al (1992) reported an inhibition of seed germination by dimethoate for some annual forbs we consider this effect to be of minor importance. First, dimethoate was sprayed on above-ground plant parts and should, therefore, not affect germination of seeds in the soil.…”
Section: Discussionmentioning
confidence: 83%
“…HowTver, tbere was no difference in the amount of totai carbon between treatments, being 43-1 '(i of dry weight in control plants (mean mvcorrhizal infection 53-8 "") and 42-7",, of dry DISCUSSION The granuiar fungicide iprodione was very effective in reducing mycorrhizal infection of plants in the field, confirming the results of otber studies (Gange, Brown & Farmer, 1990;W'est, Fitter & Watkinson, 1993). Although it may reduce seed germination (Gange, Brown & Farmer, 1992) it appears to have no toxic effect on growing plants (A. C. Gange, unpublished data), a problem which can occur with some fungicides used to reduce mycorrhizal infection (Sukarno, Smith & Scott, 1993). While we cannot discount the possibility of iprodione affecting other root-inhabiting fungi, this is unlikely to be a problem, as these were rarely seen during the mycorrhizal assessments of control plants.…”
Section: Se-g)mentioning
confidence: 99%
“…Two PPP with different modes of action were chosen in this work: the herbicide glyphosate, which acts in plants through the inhibition of 5-enolpyruvylshikimic acid 3-phosphate (EPSP) synthase (Huangfu et al, 2007) and the insecticide dimethoate which inhibits the action of Acetylcholinesterase (AChE) enzyme activity in several invertebrates (Loureiro et al, 2005a) and in some weed seeds acts through the inhibition of the synthesis or action of hydrolytic enzymes during germination (Gange et al, 1992).…”
Section: Introductionmentioning
confidence: 99%